Mild and Efficient Synthesis of Sulfonyl Fluorides from Sulfonamides Enabled by Diethylaminosulfur Trifluoride - Jurk, Friedrich; van Gemmeren, Manuel (Synlett, 2025)
A simple method for the synthesis of sulfonyl fluorides from secondary sulfonamides is described. The commercially available fluorinating agent diethylaminosulfur trifluoride (DAST) is used to efficiently transform structurally diverse secondary sulfonamides in high yields. We further demonstrate the utility of this method for the generation of sulfonamide compound libraries from a given sulfonamide starting material as well as the scalability of our method to gram scale reactions.
Keywords: Sulfonamides; DAST; Sulfonyl fluorides; SuFEx; Late-stage diversification